Psychotherapy Reduces Self Esteem Scizophrenic Patients: Literature Review - Maulana, Indra; Shalahuddin, Iwan; Eriyani, Theresia (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Low self-esteemis all the thoughts, beliefs and beliefs that an individual knows about him self and affects his relationships with others. This study aims to determine what interventions can be given to over come chronic low self-esteem problems. The method used in this research  is descriptive review by conducting literature reviews both from within and outside the country. Literature searches were carried out through several databases, namely Google Scholar, Pubmed, and Science Direct. The strategy used to search the literature is touse the keyword "chronic low self-esteem, psychotherapy, schizophrenia/schizophrenia". Based on the search, we found 839.112 articles, but after filtering the articles peryear,the complete articles and the suitability of keywords and article contents, it became 10 articles. Based on the results of the study, it can be concluded that several interventions that canbe given to reduce chronic lowself-esteem in patients with early psychotic symptoms and schizophrenia are CBT (Cognitive Behavior Therapy), EMDR (Eye Movement Desensitization and Reprocessing). GAT (Group Activity Therapy). Perceptual stimulation; told, therapy as usual (TAU) and Competitive Memory Training (COMET)/ Competitive Memory Training. Family involvement as care giver at home in the process of psychotic patient therapy can help the patient's recovery process.)